The role of glutathione redox imbalance in autism spectrum disorder: A review - Bjørklund, Geir; Tinkov, Alexey A; Hosnedlová, Božena; Kizek, Rene; Ajsuvakova, Olga P; Chirumbolo, Salvatore; Skalnaya, Margarita G; Peana, Massimiliano; Dadar, Maryam; El-Ansary, Afaf; Qasem, Hanan; Adams, James B; et al. (Free radical biology & medicine, 2020)
The role of glutathione in autism spectrum disorder (ASD) is emerging as a major topic, due to its role in the maintenance of the intracellular redox balance. Several studies have implicated glutathione redox imbalance as a leading factor in ASD, and both ASD and many other neurodevelopmental disorders involve low levels of reduced glutathione (GSH), high levels of oxidized glutathione (GSSG), and abnormalities in the expressions of glutathione-related enzymes in the blood or brain. Glutathione metabolism, through its impact on redox environment or redox-independent mechanisms, interferes with multiple mechanisms involved in ASD pathogenesis. Glutathione-mediated regulation of glutamate receptors [e.g., N-methyl-d-aspartate (NMDA) receptor], as well as the role of glutamate as a substrate for glutathione synthesis, may be involved in the regulation of glutamate excitotoxicity. However, the interaction between glutathione and glutamate in the pathogenesis of brain diseases may vary from synergism to antagonism. Modulation of glutathione is also associated with regulation of redox-sensitive transcription factors nuclear factor kappa B (NF-κB) and activator protein 1 (AP-1) and downstream signaling (proinflammatory cytokines and inducible enzymes), thus providing a significant impact on neuroinflammation. Mitochondrial dysfunction, as well as neuronal apoptosis, may also provide a significant link between glutathione metabolism and ASD. Furthermore, it has been recently highlighted that glutathione can affect and modulate DNA methylation and epigenetics. Review analysis including research studies meeting the required criteria for analysis showed statistically significant differences between the plasma GSH and GSSG levels as well as GSH:GSSG ratio in autistic patients compared with healthy individuals (P = 0.0145, P = 0.0150 and P = 0.0202, respectively). Therefore, the existing data provide a strong background on the role of the glutathione system in ASD pathogenesis. Future research is necessary to investigate the role of glutathione redox signaling in ASD, which could potentially also lead to promising therapeutics.
Keywords: Glutathione Disulfide; Oxidative Stress; glutathiondisulfid; Autistic Disorder; oxidace-redukce; lidé; Autism Spectrum Disorder; glutathion; oxidační stres; autistická porucha; Oxidation-Reduction; Glutathione; poruchy autistického spektra; Humans